PENERAPAN KOMPRES HANGAT DI DAERAH AXILLA PADA ANAK USIA PRASEKOLAH 3-6 TAHUN DENGAN THYPOID YANG MENGALAMI MASALAH HIPERTERMI DI RUANG MELATI RUMAH SAKIT TK.II DUSTIRA CIMAHI TANGGAL 01-03 MEI 2024 - Sandi; Octaviani, Oky (Jurnal Kesehatan An-Nuur, 2024)
Typhoid is an infectious disease caused by Salmonella Thypi and can be transmitted through various ways, namely Food, Fingers, Flies, Feces, and Vomitus. Typhoid is a health problem for the world community, the incidence of typhoid in Indonesia is 70% in preschool-age children. Hyperthermia is a condition in which individuals experience an increase in body temperature >37.5°C. Warm compress therapy in the axsilla is one action to reduce fever. Warm compresses are carried out 3 days for 15 minutes. The results of a case study of applying warm compresses in the axsilla showed that body temperature improved, skin temperature improved with an average decrease in fever of 1°C. The application of warm compresses in the axsilla that is carried out shows the achievement of the target indicators that have been set and a decrease in body temperature. It can be concluded that the application of warm compresses in the axsilla is effective for reducing typhoid fever in preschool-aged children. Thus the author provides advice for the public to understand the application of warm compresses in the axsilla when the child has a fever.